Trajectories of Violent Behavior Among Females and Males. Issue 1 (January 2017) - Cauffman, Elizabeth; Fine, Adam; Thomas, April G.; Monahan, Kathryn C.
Abstract : Both the psychological and criminological fields have long hypothesized the mechanisms that influence desistance from violent offending, but few studies have focused on violent females. This study identifies patterns of violent behavior across 7 years among 172 females and 172 matched males ages 15–24, testing if heterogeneity in violent offending is linked to (a) developmental change in impulse control and (b) attainment of adult milestones. Fewer females persist in violence (25%) than males (46%); 19% of males increase in violent behavior. Females who develop impulse control and are employed are more likely to desist from violence. Violent offending is unrelated to other adult milestones. Developmental increases in impulse control may trigger desistance, while employment may maintain desistance from violence.